Effects of abstract and concrete communication on moral signalling and purchase intention of upcycled food products - Danny Taufik; Raimo Rood; Hans Dagevos; Emily P. Bouwman; Machiel J. Reinders (Cleaner and Responsible Consumption, 2023)
Increasing consumer adoption of upcycled food products contributes to making the food system more resource efficient and to transitioning towards a circular economy. Yet, it is unclear how upcycled food can best be communicated towards consumers so that it signals something positive about consumers and make consumers more inclined to purchase upcycled food. In the current study, we examine to what extent upcycled foods may evoke morally self-rewarding feelings associated with purchasing upcycled food for consumers depending on (1) whether environmental or health product benefits are communicated in (2) either an abstract (generic sustainability or health lifestyle benefits) or concrete fashion (specific environmental or nutritional benefits). We found that concrete product communication led to stronger anticipated self-rewarding feelings associated with purchasing upcycled food, relative to abstract communication of either environmental or health benefits. Regardless of level of abstraction, communicating environmental (rather than health) benefits also led to stronger self-rewarding feelings. In turn, the stronger anticipated self-rewarding feelings were, the higher consumers' intention to purchase upcycled food. The findings provide marketing guidelines for companies on upcycled food: product communication about concrete environmental or nutritional benefits of upcycled food increases the extent to which consumers experience purchasing upcycled food as morally self-rewarding, which in turn is positively associated with consumers’ intention to purchase upcycled food.